Comparison of The Katarungang Pambarangay System in The Philippines With The Concept of Restorative Justice in Indonesia in Community-Based Dispute Resolution - Lusia Sulastri; Bambang Karsono; Carmelita B. Chavez; Mechelle C. Gempesao (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to analyze the comparison of dispute resolution mechanisms in the Katarungang Pambarangay system in the Philippines with the concept of restorative justice in Indonesia, as well as assess the effectiveness of both in resolving community disputes. This study uses normative legal methods with statutory approaches, conceptual approaches, and comparative approaches. The results of the study show that the Katarungang Pambarangay system regulated in Republic Act No. 7160 (Local Government Code of 1991) is a community-based mechanism that is mandatory and structured through the stages of mediation, conciliation, and arbitration by the Tagapamayapa Board. Meanwhile, restorative justice in Indonesia is an integrated approach in the formal criminal justice system based on Law Number 20 of 2025 concerning the Criminal Code, which is implemented through the authority to terminate investigations and prosecutions. In terms of effectiveness, both systems show positive results in dispute resolution. Katarungang Pambarangay has proven to be effective in increasing community participation and reducing the burden on the courts, while restorative justice in Indonesia has shown a significant increase in the number of case settlements, victim satisfaction, and the potential to suppress recidivism. The main difference lies in the nature of obligations and implementing actors, where the Philippines emphasizes the role of the community, while Indonesia relies on law enforcement officials. The study concludes that both systems have their advantages and that the integration between community-based approaches and state institutional support can be an ideal model for more effective and equitable dispute resolution.